2000
DOI: 10.1007/bf02866601
|View full text |Cite
|
Sign up to set email alerts
|

Zapotec and Mixe use of Tropical Habitats for securing medicinal plants in MéXico

Abstract: This page was generated automatically upon download from the ETH Zurich Research Collection. For more information, please consult the Terms of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
2
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 20 publications
6
23
2
8
Order By: Relevance
“…This contrasts with results from regions outside of Mesoamerica, such as Patagonia, the Caatinga of Brazil, the Himalayas and some parts of Africa (Albuquerque 2006, Adnan & Hölscher 2012, Kandari et al 2012, Molares & Ladio 2012. However, it coincides with the results of Frei et al (2000) for Isthmus Zapotecs and Mixes, and other parts of Mexico and the world (Stepp & Moerman 2001, Stepp 2004, Rokaya et al 2012. None of the medicinal species obtained from forests was sufficiently important to motivate forest conservation.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This contrasts with results from regions outside of Mesoamerica, such as Patagonia, the Caatinga of Brazil, the Himalayas and some parts of Africa (Albuquerque 2006, Adnan & Hölscher 2012, Kandari et al 2012, Molares & Ladio 2012. However, it coincides with the results of Frei et al (2000) for Isthmus Zapotecs and Mixes, and other parts of Mexico and the world (Stepp & Moerman 2001, Stepp 2004, Rokaya et al 2012. None of the medicinal species obtained from forests was sufficiently important to motivate forest conservation.…”
Section: Discussioncontrasting
confidence: 68%
“…A classification reported from the Isthmus Zapotecs and Mixes was similar in its criteria; the population distinguished village, home gardens, roadsides, maize fields, corral, pasture, coffee plantation, forest and mountains (Frei et al 2000). However, other studies report the use of physiognomy and dominant species in naming vegetation.…”
Section: Discussionmentioning
confidence: 93%
“…Voeks (1996) and Caniago & Siebert (1998) found a use pattern of medicinal resources similar to that found in the present study, which leads to the inquiry: are, in fact, primary tropical forests are rich source of medicinal resources? Those data suggest that secondary forests and disturbed areas do concentrate a large number of medicinal plants (see also Frei et al 2000). Voeks (1996) called attention to that fact and concluded that local people prefer to use the medicinal plants of disturbed areas.…”
Section: Resultsmentioning
confidence: 99%
“…We could assume that knowledge about this group of resources as foodstuffs would make some inhabitants grow and keep them in their home gardens and cultivation fields. Nevertheless, just as happens in other communities in different regions around the world, people do not take these species to their own land because they identify more abundance and diversity of these species in secondary forests and areas abandoned after cultivation (Alcorn 1981(Alcorn , 1989Hart and Hart 1986;Padoch 1987;Anderson and Posey 1989;Balée and Gély 1989;Posey 1992;Frei et al 2000;Peacock and Turner 2000). Knowledge about distribution and abundance of these resources may explain why they are obtained from some particular areas as it occurs with similar management practices developed by other groups of people (Gadgil and Berkes 1991;Berkes 1998;Berkes et al 2000).…”
Section: Discussionmentioning
confidence: 97%